Environmental Conservation and Socio-Cultural Preservation Manifestations in Tourism Policy Development in Bali - HADRIANI, Ni Luh Gede; GELGEL, I Putu; WIBAWA, I Putu Sastra (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
This study aims to analyze the function of tourism policy in regulating the balance of interests of tourism actors to guarantee the socio-cultural preservation and environmental conservation in tourism economy. This study focused on the exploration of potential of local wisdom in the tourism policy development by investigating the role model in Bali as the world most popular destination in socio-culture and environment-based tourism. The expected results are in forms of models revealing the structure and process of local wisdom-oriented tourism policy and economy that highly rely on socio-cultural and environmental preservation. It was also expected that the model considers the tourism political framework in local, national and international sphere, such as General Agreement on Trade in Services (GATS-WTO). This study was conducted by using qualitative analysis through procedures in forms of data reduction, data presentation, and drawing conclusion to obtain the results. The results showed that implementation of tourism policy rely on accommodative regulation on the socio-cultural and environmental orientation in local context, aligning with national interest and international tourism development. The local wisdom of the Balinese society has been potential in the policy tourism development, among in the tourism policy substance, structure, and culture. The socio-economic-oriented tourism development policy should rely on appropriate policy making, stakeholder collaboration and ensure tourism business sustainability as well as to ultimately ensure the preservation of local culture and the conservation of environment.